"Direct and indirect impacts of the COVID-19 pandemic on operational conduct of pediatric vaccine clinical trials" - Monica Anne McArthur; Siham Bchir; Estelle Dubois; Lucia Gan; Eric Gerchman; Sandeep Gupta; Olga Liabis; Lucia Perez; Fabienne Roche; Gustavo Vasquez; Betzana Zambrano; Sanjay Gurunathan; et al. (Taylor & Francis Group, 2023)
ABSTRACTThe coronavirus 2019 (COVID-19) pandemic, as well as the resulting public health measures, impacted many aspects of society. The conduct of important pediatric vaccine trials was among these. Analyzing data from six ongoing non-COVID-19 pediatric vaccine trials we aimed to assess the operational impact of the COVID-19 pandemic using descriptive analyses. We identified multiple operational disruptions in trial conduct. Additionally, we identified higher percentages of missed routine vaccinations than investigational vaccines throughout the observation period. Overall, the impact of the COVID-19 pandemic was most apparent early in the pandemic period while adaptations to the pandemic were developed; however, some disruptions persisted throughout the observation period. Pediatric vaccine clinical trials are critical to developing new and/or improved vaccines for the pediatric population. Continued evaluation of the impacts of COVID-19 on pediatric vaccine clinical trials is warranted.